Developing a vision of society: Transformative learning and the emancipatory process - Kathleen Loughlin (Adult Education Research Conference, 1993)
A qualitative study of women change agents suggests an envisioning process as a significant dynamic in commitment-making. This finding and the transformative learning which facilitated it are reviewed.